Corporate sexual equality and firm performance. (30th January 2017) - Shan, Liwei; Fu, Shihe; Zheng, Lu
Abstract : Research summary: Previous studies have mixed findings on the relation between corporate socially responsible policies and firm performance. This paper focuses on a specific type of corporate social responsibility—corporate sexual equality, measuring how a firm treats its lesbian, gay, bisexual, and transgender (LGBT) employees, consumers, and investors—and examines whether and how it relates to firm performance. Using a longitudinal dataset of public firms in the U.S. during the period of 2002–2006, we demonstrate that firms with a higher degree of corporate sexual equality have higher stock returns and higher market valuation. We also identify one of the mediating channels, the labor market channel, that brings higher productivity to firms that embrace sexual equality . Managerial summary: Corporate sexual equality measures how a company treats its lesbian, gay, bisexual, and transgender (LGBT) employees, consumers, and investors. It is an important dimension of corporate social responsibility policies and diversity management. Using a longitudinal dataset of public firms in the U.S. during the period of 2002–2006, we demonstrate that firms with a higher degree of corporate sexual equality have higher stock returns, higher market valuation, and higher labor productivity. Our findings suggest that discriminatory hiring behaviors based on sexual orientation hurt employers and shareholders financially and that implementing corporate sexual equality policies can enhance firms' financial performance, generating competitive advantages in labor markets and mutual benefits between employers and employees . Copyright © 2016 John Wiley & Sons, Ltd.